1998
DOI: 10.1080/02786829808965556
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Sized Particle Formation from NH3/SO2/H2O/Air Mixtures by Ionizing Irradiation

Abstract: ABSTRACT. Formation of nanometer-sized particles in NH,ISOJH,OIAir mixtures by a-ray irradiation was studied experimentally to evaluate the effect of NH, gas on the gas-to-particle conversion process. The total particle number concentration, the charged-particle fraction, and the electrical mobility distribution of particles generated in the ionization chamber were measured at various NH,, SO,, and H,O vapor concentrations and residence times of the gas mixture. Particle generation was enhanced in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 40 publications
8
60
1
Order By: Relevance
“…Therefore, both O-TDMA measurements and H-TDMA measurements confirm that the particles produced in these conditions consisted of ammonium sulphate at a diameter of 150 nm. These results are in good agreement with earlier studies, as the particles formed by nucleation eventually become chemically neutral and form salt particles, such as ammonium bisulphate and ammonium sulphate if the ammonia concentration is high enough (Seinfeld and Pandis, 1998;Kim et al, 1998). Fig.…”
Section: Particle Composition In the Presence Of Sulphuric Acid And Asupporting
confidence: 82%
“…Therefore, both O-TDMA measurements and H-TDMA measurements confirm that the particles produced in these conditions consisted of ammonium sulphate at a diameter of 150 nm. These results are in good agreement with earlier studies, as the particles formed by nucleation eventually become chemically neutral and form salt particles, such as ammonium bisulphate and ammonium sulphate if the ammonia concentration is high enough (Seinfeld and Pandis, 1998;Kim et al, 1998). Fig.…”
Section: Particle Composition In the Presence Of Sulphuric Acid And Asupporting
confidence: 82%
“…Firstly the charged fractions were examined and secondly the electrical mobility distributions for positive and negative particles revealed a stronger activation by negative ions. In later work by the same group (Kim et al, 1998) the presence of NH 3 was found to enhance particle formation and decrease the charged fraction.…”
Section: Bulk Nucleationmentioning
confidence: 99%
“…Even if the system has multiple chemical species, it cannot be simply assumed that nucleation would take place through THN or multicomponent processes; rather it depends on several conditions including how much these ternary species are present in the system, and sometimes nucleation can take place solely via BHN even in the presence of ternary species (McGraw and Zhang, 2008). A laboratory study has also shown that different mechanisms may occur with the same aerosol precursors, under different experimental conditions (Kim et al, 1998). A typical atmospheric example would be the upper troposphere and lower stratosphere; even when there are many other chemical species in the gas phase, ion induced nucleation dominates in this region , because of low temperatures and high ion production rates by cosmic rays.…”
Section: Thn Effectsmentioning
confidence: 99%
“…At present, the exact [NH 3 ] needed to enhance J over BHN and the magnitude of enhancement in nucleation due to NH 3 are both uncertain, mostly because there are only a very limited number of laboratory studies of NH 3 -THN (Ball et al, 1999;Benson et al, 2009;Berndt et al, 2010;Hanson and Eisele, 2002;Kim et al, 1998). To produce particles, these experiments also used [H 2 SO 4 ] > 10 8 cm −3 , two to three orders of magnitude higher than typical atmospheric concentrations (10 5 -10 7 cm −3 ) (Erupe et al, 2010;McMurry et al, 2005 [OH] in the nucleation reactor), estimation of wall loss of aerosol precursors and nucleation time in the nucleation reactor, and particle detection with different cutting sizes.…”
Section: Introductionmentioning
confidence: 99%